Islamic Partnership-Based Financing and Financial Sustainability for Micro Enterprises in Mogadishu, Somalia - Sharmarke Mohamed Ali; Ayub Mukhtar Adam; Hodan Abdullahi Farah (Talaa : Journal of Islamic Finance, 2025)
It is specifically focused on examining; (i) the relationship between Mudarabah financing and micro enterprise finance sustainability (ii) the relationship between Musharakah financing and micro enterprise finance sustainability and (iii) the relationship between Musharakah Mutanaqisah financing and micro enterprise finance sustainability in Mogadishu, Somalia. A correlational research design was used in the investigation. There were 248 respondents selected using a random sampling technique directly from a population of 701 micro-enterprises in Mogadishu. Statistics were collected using self-administered surveys and analyzed by the SPSS program after Pearson's correlation analysis. It reveals that; (i) there was a statistically significant positive relationship between Mudarabah financing and the financial sustainability of micro enterprises, (ii) there was a statistically significant positive relationship between Musharakah financing and the financial sustainability of micro enterprises and (iii) there was a statistically substantial optimistic relationship between Musharakah Mutanaqisah financing and the financial sustainability of micro Therefore, the study concludes that the provision of Islamic partnership-based financing involving Mudarabah, Musharakah and Musyarakah Mutanaqisah financing can increase the financial sustainability of micro-enterprises in Mogadishu, Somalia